#TITLE_ALTERNATIVE# - ODE MUHAMMAD GOLOK JAYA (NIM 25107001), LA
Determination of carbon stock in a certain area is very important since its relation to the global warming and clean development mechanism issues. Indonesia which has the biggest tropical forest in the world after Brazil needs to develop the model of forest monitoring and inventory to endorse the decreasing of green house gases emission and clean development mechanism as well. Forest has become the most important place where the carbon compound (CO2 and CO) exchange took place. Forest vegetation absorbs carbon during photosynthesis to develop biomass where carbon becomes a half part of it. It means that forest management status will determine whether the forest acts as source of carbon emission or sink. This research was aimed to inventory carbon stock of Pinus merkusii in forest protection area of BKPH Manglayang Barat using Small Format Aerial Photograph (SFAP) and SPOT-5 imagery. The three most important parameters to determine the carbon stock are stand diameter (DBH = Diameter at Breast Height), crown diameter and spectral reflectance respectively. These parameters can be obtained directly from SFAP. The result of this research showed that SFAP can be used to inventory the carbon stock of Pinus merkusii moderately. SFAP ground resolution, various from 8 to 12 cm depend the flight height, can assist us to determine stand diameter and crown diameter easily. Stand diameter can be identified and measured simply with more than 90% level of confidence. Also, the crown diameter can be identified and measured using SFAP with more than 84% level of confidence. The SFAP spectral reflectance can be used also to determine the health and stress of the pine leaf. The research showed us that the SFAP is moderately can be used as sample area of SPOT-5 imagery to determine the distribution of carbon stock in the wide area. There was a good spectral correlation between SFAP and SPOT-5 imagery in the 81% level of confidence. The SFAP also can be used as sample area to determine the age of Pine stand in the SPOT-5 imagery with 65% level of confidence. The aerial photograph taken from the R/C plane model, as one of alternative method to collect land cover data, can increase the reliability of SPOT land cover classification in estimating the carbon stock. The carbon stock determination from directly measurement of pine stand diameter using SFAP has a good result which only 14.63% (R2 = 0,916) difference close to field survey. In accordance with this result, carbon stock determination through indirectly measurement using canopy diameter also has a good indication. The result showed us 18,56% (R2 = 0,8073) difference close to field survey. Based on these results we may conclude that SFAP is reliable to determine the carbon stock.